Evaluation of a Codesign Method Used to Support the Inclusion of Children With Disability in Mainstream Schools. (15th April 2020) - Hyett, Nerida; Bagley, Kerryn; Iacono, Teresa; McKinstry, Carol; Spong, Jo; Landry, Oriane
Codesign is increasingly used for health research and service improvement. Codesign combines generative and exploratory methods, enabling collaboration between service end users and researchers as equal partners. The aim of this study was to evaluate a codesign method used to design an online education package about inclusive education for children with disability in mainstream schools. The study design was a multiple methods evaluation informed by participatory and transformative research paradigms, incorporating design sciences and public service approaches. A governance committee supported the process. The codesigners ( n = 12) included teachers, teacher assistants, parents, and allied health professionals. Process and outcome evaluation data were used; data collected were from verbatim transcripts of codesign workshop discussions ( n = 11), documents, Self-Report Level of Participation Surveys, and individual interviews ( n = 11). Thematic and descriptive analysis methods were used to describe the codesign processes, experiences, and outcomes. The key processes were identifying the issues through storytelling, voicing frustrations, being vulnerable, sharing insider knowledge, challenging other people's roles, and deliberation and decision-making . Codesigners' experiences and outcomes identified strengths and challenges in the method. A conceptual model is presented demonstrating interrelationships between processes, subprocesses, and codesigners' experiences and outcomes. Codesign involves multiple, interrelated processes that support deliberation and creative design. Skills and resources are required to effectively facilitate what can be a meaningful, creative, and social process.